Deep Brain Stimulation Initiative: Toward Innovative Technology, New Disease Indications, and Approaches to Current and Future Clinical Challenges in Neuromodulation Therapy - Sui, Yanan; Tian, Ye; Ko, Wai Kin Daniel; Wang, Zhiyan; Jia, Fumin; Horn, Andreas; De Ridder, Dirk; Choi, Ki Sueng; Bari, Ausaf A.; Wang, Shouyan; Hamani, Clement; Baker, Kenneth B.; et al. (Frontiers in Neurology, 2021)
Deep brain stimulation (DBS) is one of the most important clinical therapy for neurological disorders. DBS also has great potential to become great tools for the research of clinical neuroscience. Recently, the National Engineering Laboratory for Neuromodulation at Tsinghua University held an international Deep Brain Stimulation Initiative workshop to discuss the cutting-edge technological achievements and clinical applications of deep brain stimulation. We specifically addressed new clinical approaches and challenges in DBS for movement disorders (Parkinson’s disease and dystonia), clinical application towards neurorehabilitation for stroke; and the progress and challenges towards DBS for neuropsychiatric disorders. This review highlighted key developments in: 1) neuroimaging, with advancements in 3-Tesla Magnetic Resonance Imaging DBS compatibility for exploration of brain network mechanisms, 2) novel DBS recording capabilities for uncovering disease pathophysiology and 3) overcoming global healthcare burdens with online-based DBS programming technology for connecting patient communities. The successful event marks a milestone for global collaborative opportunities in clinical development of neuromodulation to treat major neurological disorders.